Steeper social discounting after human basolateral amygdala damage - Tobias Kalenscher; Luca M. Lüpken; Ron Stoop; David Terburg; Jack van Honk (Proceedings of the National Academy of Sciences, 2025)
Translational research suggests that the basolateral part of the amygdala (BLA) computes some of the core processes underlying social preferences, but its precise role in prosocial choice remains unclear. We hypothesize that the human BLA is not necessary for prosocial behavior per se, but fine-tunes the degree of prosociality as a function of the social distance between actor and recipient of a prosocial act. We tested five participants with Urbach–Wiethe disease (UWD) who had isolated, bilateral damage to BLA and compared their behavior in a modified dictator game to that of 16 healthy control participants matched for (neuro-) psychological traits and cultural and socioeconomic background. In this game, participants selected eight people from their social environment and assigned them to variable social distance levels ranging from 1 (emotionally closest person) to 100 (random stranger on the street). They decided how much of a monetary endowment they would share with each person at each social distance. Compared to controls, UWD participants were less generous overall and showed steeper social discounting, that is, their willingness to share declined more sharply with increasing social distance. This difference in social discounting could not be explained by empathy, personality, or social network size. Our data suggest that BLA is critical for resolving the conflict between selfish and altruistic motives during social discounting. This finding underlines the BLA’s role in model-based social cognition, calibrating prosocial behavior based on the social-emotional distance between individuals.